KEY SUCCESS VALUES IN RELATIONSHIP MARKETING OF AGRICULTURE PRODUCTS - Muchlis Ahmady; Ujang Sumarwan; Budi Suharjo; Agus Maulana (School of Business, Bogor Agricultural University (SB-IPB), 2012)
In Indonesia, agriculture is still one of the business activity that involves many stakeholders with a unique relationship, ranging from farmers as producers, various intermediaries that act to move the product on the retailers who ultimately sell to end consumers. What are the key values connecting between actors to guarantee the continuity of business and how the model linkage or relationship marketing that happens, is the main goal in this paper. The results showed, commitment and trust are the dominant two aspects that underlie the emergence of co-operation as well as the assurance of financial benefit. Another interesting fact revealed by this study is the relationship marketing that occurs not just based on the transactional aspects alone, but there is also a social aspect that binds relationships. This aspect even leads to another fundamental goal, namely the existence of convenience between the parties cooperate. Although both of these goals cannot always be achieved simultaneously due to the strata of different decision-making power, but in reality they complement the ongoing collaboration.Keywords: Commitment, Trust, Transactional and Social Marketing, Leisure